32P A comprehensive tumour immunogenomics platform for precision immunotherapy: Enabling simultaneous characterization of tumours and the TME from a single FFPE sample. (15th December 2019) - Power, R; Bartha, G; Harris, J; Boyle, S M; Levy, E; Milani, P; Tandon, P; Li, R; Chinnappa, M; Haddad, A; McNitt, P; McClory, R; et al.
Abstract: Background: Immunogenomic profiling of the tumour and the TME is critical for identifying biomarkers of immunotherapy response and understanding resistance. However, running many assays for each sample is impractical given limited sample quantity, processing complexity, and prohibitive cost. To address this, we developed a novel, augmented exome-/transcriptome-based tumour immunogenomics platform. Methods: We optimized the design of our sequencing assays and analytics for improved somatic SNV, indel, CNA, and fusion detection across ∼20, 000 genes, and for the evaluation of neoantigens, expression signatures, HLA typing and LOH, TCR/BCR repertoires, oncoviruses, TILs, clinically-actionable mutations, TMB, and MSI status. Results: With 25ng of DNA per FFPE sample and co-extracted RNA, this platform completely covers between 17-40% more genes compared to a non-augmented exome; increasing sensitivity to somatic mutations and neoantigens. For neoantigen detection, we generated immunopeptidomic data from monoallelic HLA transfected cell lines and trained neural networks to predict neoepitope binding to MHC; demonstrating higher precision (0.88) across alleles than publicly-available tools (0.9 and >0.94, respectively). For TILs, we developed signatures for immune cells, demonstrating concordance with CyTOF-derived validation sets. We achieve HLA typing accuracy of 99.1% for Class I and 95% for Class II calls, and have developed a novel tool for HLA LOH evaluation. We achieve sensitive detection of oncoviruses, as well as accurate MSI and TMB assessment. For diagnostic reporting, we report high sensitivity and specificity for clinically-reportable mutations comparable with diagnostic cancer panels. Conclusion: We have developed a novel tumour immunogenomics platform that simultaneously profiles the tumour and TME from a single sample. Legal entity responsible for the study: Personalis, Inc. Funding: Personalis, Inc. Disclosure: R. Power: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. G. Bartha: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. J. Harris: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. S.M. Boyle: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. E. Levy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. P. Milani: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. P. Tandon: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. R. Li: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. M. Chinnappa: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. A. Haddad: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. P. McNitt: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. R. McClory: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. M. Morra: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. S. Saldivar: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. M. Clark: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. C. Haudenschild: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. E. Newburn: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. C. Johnson: Shareholder / Stockholder / Stock options, Full / Part-time employment: Personalis, Inc. R. Chen: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: Personalis, In J. West: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: Personalis, Inc.